2013
DOI: 10.3727/096368912x655019
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Cultured Adipose Tissue-Derived Stromal Cells Ameliorate Acute Kidney Injury in Rats

Abstract: Current studies suggest that mesenchymal stromal cells (MSCs) improve acute kidney injury (AKI) via paracrine/endocrine effects. We established human adipose tissue-derived stromal cells (hASCs) cultured in low (2%) serum (hLASCs), which have great potential of tissue regeneration. The present study was performed to investigate the therapeutic effects of hLASCs on AKI and to clarify the mechanisms involved. In low serum, hASCs proliferated well, while human bone marrow-derived stromal cells (hBMSCs) did not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…As reported before that MSCs reduced the production of TNF-α which mediated the deposition of extracellular matrix in the renal interstitium by the myofibroblasts [10,19] .…”
Section: Discussionmentioning
confidence: 61%
“…As reported before that MSCs reduced the production of TNF-α which mediated the deposition of extracellular matrix in the renal interstitium by the myofibroblasts [10,19] .…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, in a model of cisplatin-induced AKI, mouse ASCs, as well as their CM, showed protective effects by decreasing kidney injury and tubular cell apoptosis, and increasing mouse survival (2). With regard to human ASCs for renal protection/ repair, one study demonstrated their ability to protect recipient nude rats from folic acid-induced kidney injury and subsequent fibrosis (22). Also, an investigation using a rat model of cisplatin-induced nephrotoxicity revealed that intravenous delivery of hASCs led to lower renal damage and dysfunction, as well as higher survival (24).…”
Section: Discussionmentioning
confidence: 99%
“…14,15,32 Systemic or local administration of LASCs improved rat ischemic hind limb injury 15 and folic acid-induced acute renal tubular injury, 32 and impeded production of antibodies against exogenous porcine red blood cells. 14 Moreover, LASCs produce higher amounts of hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) in vitro than HASCs (Supplemental Figure 1C).…”
Section: Low-serum Culture Conditions Amplify the Renoprotective Effementioning
confidence: 99%